More of a Good Thing Is Even Better: Examining the Dimensions of Hedonic and Eudaimonic Savouring, and Their Interrelations with Motivation Self-Regulation and Well-Being - Lauzon, André (Université d'Ottawa / University of Ottawa, 2018)
Savouring is the capacity to focus on pleasant experiences in order to intensify and prolong the experience of positive affect. Although the mechanisms and processes of savouring have been studied, the components of its very nature have been largely neglected. The primary objective of this project was thus to develop and validate a taxonomy of savouring comprising seven dimensions: hedonic savouring, and eudaimonic savouring of meaning of life, spirituality, inspiration, self-reflection, appreciation, and gratitude. To achieve this objective, a new measure was developed: the Savouring Configuration Inventory (SCI). In Study 1, 190 participants completed the initial extended version of the SCI, which was reduced and revised on the basis of the results of an exploratory factor analysis. In Study 2 (N=350), the factorial structure of the final version of the SCI, comprising 28 items (4 items/subscales), was successfully tested using a confirmatory factor analysis, and its complementary metric properties (internal consistency, construct, concurrent, and discriminant validity) were documented. The second goal of this project was to examine the associations among motivation, hedonic and eudaimonic savouring, and well-being. Study 3 (N=283) was designed to evaluate the network of relationships between these variables using a structural equation model. Results revealed that intrinsic motivation was associated with hedonic and eudaimonic savouring, while self-determined extrinsic motivation was associated solely with eudaimonic savouring. Eudaimonic savouring was the highest predictor of well-being, although intrinsic motivation was also moderately associated to this outcome. Contrary to hypotheses, self-determined extrinsic motivation and hedonic savouring did not display unique associations with well-being. Although significant correlations were obtained between these constructs, when both forms of motivation and savouring were concurrently tested as predictors of well-being, eudaimonic savouring and intrinsic motivation predominated. The overall fit of the final structural model was satisfactory. Findings from this project hold important fundamental implications, as they contribute original information on the nature and configuration of the dimensions of savouring experiences, and on their associations with motivational antecedents and well-being consequences.
Keywords: Savouring; Savouring experiences; Motivation; Self-determination; Well-being